Farming in the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Improvement and development of traditional farming systems for the South Pacific. Proceedings of an IRETA Workshop, 18 22 October 1999. IRETA, 2001. 158 pp. ISBN 982 175 136 9 US$ 20 Euro 22.32